2004
DOI: 10.1128/aem.70.7.4222-4229.2004
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Stress Response: Quantification of Cell Maintenance and Metabolic Fluxes in a Lysine-Overproducing Strain of Corynebacterium glutamicum

Abstract: Osmotic stress diminishes cell productivity and may cause cell inactivation in industrial fermentations. The quantification of metabolic changes under such conditions is fundamental for understanding and describing microbial behavior during bioprocesses. We quantified the gradual changes that take place when a lysineoverproducing strain of Corynebacterium glutamicum is grown in continuous culture with saline gradients at different dilution rates. The use of compatible solutes depended on environmental conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…On the other hand, OaA node exhibited relative inflexibility as evident from no substantial change in the flux partitioning. The last observation is in agreement with the results reported by Varela et al [32], who reported that OaA shows rigidity up to 1,000 mosmol/kg [32,33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, OaA node exhibited relative inflexibility as evident from no substantial change in the flux partitioning. The last observation is in agreement with the results reported by Varela et al [32], who reported that OaA shows rigidity up to 1,000 mosmol/kg [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…Varela et al [32] for the first time quantified metabolic response in terms of metabolic flux redistribution in C. glutamicum grown under discrete and gradient continuous culture to gradually increasing osmolarity (between 270 and 1,880 mosmol/kg). Varela et al [33] also estimated the alteration in the maintenance coefficients of substrate and ATP under osmotic stress conditions using flux balance analysis. In the current study, we aim to quantify the metabolic fluxes across the network using the elementary mode approach.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the excess glucose is diverted toward overflow metabolites. The high ratio of anaplerotic to catabolic fluxes is a striking fact, especially if we consider that thriving under osmotic stress is usually energetically expensive, especially in microorganisms that use the organicsolutes-in strategy (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…This included Y X/ATP 510.5 g mol 21 (de Hollander, 1994). For the P : O ratio, earlier estimates range between 1.5 and 2.0, so that here a mean value of 1.75 was assumed (de Hollander, 1994;Varela et al, 2003Varela et al, , 2004.…”
mentioning
confidence: 99%